"EXPLORING THE IMPACT OF OCCUPATIONAL STRESS ON COLLEGE TEACHERS: A CONCEPTUAL PERSPECTIVE" (International Journal of Food and Nutritional Sciences, 2022)
Occupational stress, often referred to as job stress or work stress, is an inherent challenge in the modern work environment, significantly impacting employees' well-being, productivity, and overall job satisfaction. Occupational stress is a significant concern in the teaching profession, particularly among college educators who face multiple challenges in their work environment. This conceptual study explores the factors contributing to occupational stress, its impact on teachers' job performance and well-being, and possible coping strategies. Using a qualitative approach based on secondary data, the study reviews existing literature to identify key stressors such as workload, administrative pressures, job insecurity, and work-life imbalance. The findings highlight how prolonged exposure to stress can lead to burnout, reduced job satisfaction, and declining mental and physical health. Additionally, the study discusses effective coping mechanisms, including institutional support, time management techniques, and psychological resilience-building strategies. By synthesising existing research, this paper provides valuable insights into mitigating occupational stress among college teachers, ultimately aiming to enhance their professional effectiveness and overall well-being.